River-floodplain connectivity and residence times controlled by topographic bluffs along a backwater transition - Tull, Nelson; Moodie, Andrew J.; Passalacqua, Paola (Frontiers in Water, 2024)
The morphology of river levees and floodplains is an important control on river-floodplain connectivity within a river system under sub-bankfull conditions, and this morphology changes as a river approaches the coast due to backwater influence. Floodplain width can also vary along a river, and floodplain constrictions in the form of bluffs adjacent to the river can influence inundation extent. However, the relative controls of backwater-influenced floodplain topography and bluff topography on river-floodplain connectivity have not been studied. We measure discharge along the Lower Trinity River (Texas, USA) during high flow to determine which floodplain features are associated with major river-floodplain flow exchanges. We develop a numerical model representing the transition to backwater-dominated river hydraulics, and quantify downstream changes in levee channelization, inundation, and fluxes along the river-floodplain boundary.We model passive particle transport through the floodplain, and compute residence times as a function of location where particles enter the floodplain. We find that bluff topography controls flow from the floodplain back to the river, whereas levee topography facilitates flow to the floodplain through floodplain channels. Return flow to the river is limited to locations just upstream of bluffs, even under receding flood conditions, whereas outflow locations are numerous and occur all along the river. Residence times for particles entering the floodplain far upstream of bluffs are as much as two orders of magnitude longer than those for particles entering short distances upstream of bluffs. This study can benefit floodplain ecosystem management and restoration plans by informing on the key locations of lateral exchange and variable residence time distributions in river-floodplain systems.